2008
DOI: 10.1002/ijc.23344
|View full text |Cite
|
Sign up to set email alerts
|

Non‐Hodgkin lymphoma and obesity: A pooled analysis from the InterLymph Consortium

Abstract: Nutritional status is known to alter immune function, a suspected risk factor for non-Hodgkin lymphoma (NHL). To investigate whether long-term over, or under, nutrition is associated with NHL, self-reported anthropometric data on weight and height from over 10,000 cases of NHL and 16,000 controls were pooled across 18 case-control studies identified through the International Lymphoma Epidemiology Consortium. Study-specific odds ratios (OR) were estimated using logistic regression and combined using a random-ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
76
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(87 citation statements)
references
References 50 publications
(112 reference statements)
11
76
0
Order By: Relevance
“…All cases and controls (416 and 181 cases, and 2,260 and 966 controls in HER-PACC-I and HERPACC-II, respectively) pooled in the analysis of the InterLymph study were included in our study. 1 Our previous study confirmed the feasibility of using noncancer outpatients at our hospital as controls in epidemiological studies because their general lifestyles are accordant with those of a general population randomly selected from the electoral roll in Nagoya City. 32 Although the ACCH is called a cancer hospital, only 20 and 11% of all new male and female outpatients have cancer.…”
Section: Cases and Controlssupporting
confidence: 67%
See 1 more Smart Citation
“…All cases and controls (416 and 181 cases, and 2,260 and 966 controls in HER-PACC-I and HERPACC-II, respectively) pooled in the analysis of the InterLymph study were included in our study. 1 Our previous study confirmed the feasibility of using noncancer outpatients at our hospital as controls in epidemiological studies because their general lifestyles are accordant with those of a general population randomly selected from the electoral roll in Nagoya City. 32 Although the ACCH is called a cancer hospital, only 20 and 11% of all new male and female outpatients have cancer.…”
Section: Cases and Controlssupporting
confidence: 67%
“…[1][2][3][4][5][6][7][8][9][10][11] Moreover, most of these studies were conducted in non-Asian populations. Recently, the International Lymphoma Epidemiology Consortium (InterLymph) reported a large pooled analysis of 18 case-control studies conducted at various centers, including ours, to evaluate the impact of recent obesity on NHL risk, with the results suggesting no significant association between NHL and obesity.…”
mentioning
confidence: 99%
“…These results were in agreement with the findings of the study by Larsson and Wolk (17) in Sweden in 2011 as well as those by Litchman et al (18) in the United States in 2010 indicating where the BMI was positively associated with the increased risk of the NHL and the HL. The given findings were also consistent with the results of the study by Willet et al (19) suggesting that individuals with the BMI equal or more than 30, five years before the diagnosis of their disease had a greater risk of infection with HL. In a way that it was argued to have an initial focus on the prevention of cancer to reduce obesity.…”
Section: Discussionsupporting
confidence: 92%
“…[17][18][19][20][21][22][23][24][25][26] Results from a meta-analysis by Larsson et al indicate that excess body weight may be a risk factor for NHL and MM, 27,28 whereas a pooled analysis from the InterLymph Consortium found no evidence to support the hypothesis that obesity is a determinant of all types of NHL combined. 29 Of the 19 published reports, [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] seven cohort studies focused on incident cases 10,[18][19][20][21][22]26 and two cohorts focused on mortality. 8,11 Although sexspecific 8,9,11,14,15,18,19,…”
Section: Introductionmentioning
confidence: 99%